PRAKTIK BAGI HASIL TERNAK SAPI PERSPEKTIF HUKUM EKONOMI SYARIAH - Tehedi Tehedi; Ervannio Ervannio (Borneo : Journal of Islamic Studies, 2021)
The implementation of the determination of the profit-sharing ratio in the cooperation contract for the maintenance of cattle in Sebubus Village, Paloh District, indicates that there is no clarity regarding the issue of the contract, rights, obligations of the parties, and profit-sharing. Based on this, it is necessary to study in more depth how the actual practice of cooperative cattle rearing in Sebubus Village, Paloh District is and how the sharia economic law reviews the practice of such cooperation. This study uses a qualitative research type with an empirical normative approach. The results of the study concluded that the implementation of cooperation in raising cattle in Sebubus Village began with an agreement between the two parties verbally to cooperate with cattle where the shahibul mal (capital owner) provided the cows and the mudharib (manager) was responsible for raising the cattle. Provisions on the ratio of profit sharing where the first calf born by the mother cow becomes the full property of the cow keeper. Furthermore, the second calf produced by the mother cow becomes the full share for the owner of the capital, and so on. The perspective of sharia economic law on the practice of cooperation is basically harmonious and the terms of the contract have been fulfilled, but it is necessary to clearly and in detail the rights, obligations, ratios, and the possibility of loss or default by making a written contract.